Topical niclosamide (ATx201) reduces Staphylococcus aureus colonization and increases Shannon diversity of the skin microbiome in atopic dermatitis patients in a randomized, double‐blind, placebo‐controlled Phase 2 trial. Issue 5 (6th May 2022) - Weiss, Anne; Delavenne, Emilie; Matias, Carina; Lagler, Heimo; Simon, Daniel; Li, Ping; Hansen, Jon U.; dos Santos, Teresa Pires; Jana, Bimal; Priemel, Petra; Bangert, Christine; Bauer, Martin; et al.
Abstract: Background: In patients with atopic dermatitis (AD), Staphylococcus aureus frequently colonizes lesions and is hypothesized to be linked to disease severity and progression. Treatments that reduce S. aureus colonization without significantly affecting the skin commensal microbiota are needed. Methods and findings: In this study, we tested ATx201 (niclosamide), a small molecule, on its efficacy to reduce S. aureus and propensity to evolve resistance in vitro. Various cutaneous formulations were then tested in a superficial skin infection model. Finally, a Phase 2 randomized, double‐blind and placebo‐controlled trial was performed to investigate the impact of ATx201 OINTMENT 2% on S. aureus colonization and skin microbiome composition in patients with mild‐to‐severe AD (EudraCT:2016‐003501‐33). ATx201 has a narrow minimal inhibitory concentration distribution (.125–.5 μg/ml) consistent with its mode of action – targeting the proton motive force effectively stopping cell growth. In murine models, ATx201 can effectively treat superficial skin infections of methicillin‐resistant S. aureus . In a Phase 2 trial in patients with mild‐to‐severe AD ( N = 36), twice‐daily treatment with ATx201 OINTMENT 2% effectively reduces S. aureus colonization in quantitative colony forming unit (CFU) analysis (primary endpoint: 94.4% active vs. 38.9% vehicle success rate, p = .0016) and increases the Shannon diversity of the skin microbiome at day 7 significantly compared to vehicle. Conclusion: These results suggest that ATx201 could become a new treatment modality as a decolonizing agent. Abstract : ATx201 reduces S.aureus in vitro and in vivo with a narrow MIC distribution consistent with its mode of action targeting the proton motive force effectively stopping cell growth. In a Phase 2 trial in patients with mild‐to‐severe AD, twice‐daily treatment with ATx201 OINTMENT 2% effectively reduces S. aureus colonization and increases the Shannon diversity of the skin microbiome at day 7 significantly compared to vehicle. Thus, ATx201 could become a new treatment modality as a decolonizing agent.